Synthesis and X-Ray Crystal Structure of 1,1'-Bis(diphenyphosphino)ferrocene Supported CuSCF3 Complex - Yang, Yi; Luo, Gen; Tong, Xia; Shu, Yu-Mei; Zheng, Yu-Bing (Asian Journal of Chemistry, 2019)
We report herein the synthesis of CuSCF3 complex supported by 1,1'-bis(diphenyphosphino)ferrocene via deoxygenative reduction of Langlois reagent (CF3SO2Na). This cuprous complex [(dppf)Cu(SCF3)] was fully characterized by elemental analysis and 1H (13C, 19F, 31P) NMR spectra. In addition, the molecular structure of [(dppf)Cu(SCF3)] was established by X-ray crystallography. The crystal of compound 1 crystallizes in monoclinic, space group P21/n with a = 11.4366(9), b = 19.1340(16), c = 14.0625(11) Å, V = 3072.62(2) Å3, Z = 4, Z’ = 0, C35H28CuF3FeP2S, Mr = 719.00 and R-factor = 3.69. The short contacts between the two fluorine atoms of CF3S moiety and aromatic hydrogen of Cp/(Ph) rings were observed with leaving the sterically-congested fluorine untouched which highly resembled to the sibling [(PPh3)2CuSCF3]. These interesting secondary interactions in the crystal lattice were explained by the electrostatic forces in terms of the strong dipole of C-F bonds.